DAMPAK COVID-19 TERHADAP PENDAPATAN USAHA PEDAGANG KAKI LIMA DI LAPANGAN GEDUNG OLAHRAGA SUDIANG KOTA MAKASSAR - Nuraisya, Siti; Diana, Fina (Universitas Patria Artha, 2023)
The Covid-19 pandemic has brought many impacts in various fields of life in Indonesia, one of which is the economic sector. In the economic field, there is a decrease in income due to at least buying andbselling that is felt by all groups in society. Street vendors (PKL) who belong to the informal group alsobfeel the impact of this pandemic. Since the government issued the Large-Scale Social Restriction (PSBB) policy, this has made street vendors lose their buyers, which resulted in a decrease in income.The purpose of this study is to describe the impact of COVID-19 on street vendors (PKL) in the Sudiang Sports Building field, Makassar City so that they can survive in the midst of the COVID-19 pandemic and describe the strategies used during the pandemic.The research method used is qualitative. The results of this study are (1) the loss of buyers and customers because when the PSBB policy is implemented people prefer to stay at home and are reluctant to leave the house if it is not important. (2) This decrease in income is a follow-up impact when buyers are reduced because it will automatically reduce their income as well. (3) Street vendors make strategies sothat they can maintain their business and fulfill their daily needs